High frequency of germinal centre derivation in diffuse large B cell lymphoma from Asian patients. - Shia, A.K.H.; Gan, G-G.; Jairaman, S.; Peh, S-C. (BMJ Publishing Group, 2005)
It may be possible to stratify patients for treatment using markers for specific lineages of B cell differentiation.